Jalan Herodes atau Majus? Implikasi Kisah Kelahiran Kristus di Matius Matius 2:1-12 Bagi Penuntasan Amanat Agung - Setianto, Yusak; Abrillian, Melvin; Wariki, Valentino (Sekolah Tinggi Teologi Transformasi Indonesia, 2023)
Abstract: The church today often experiences difficulties completing the Great Commission because most only move from one congregation to another. This research aims to explore the responses of the magi and Herod to the news of Christ's birth in Matthew 2:1-12 which is associated with the completion of the Great Commission. The research method used is descriptive qualitative based on a literature study. The study results show that the story offers two paths: the